Differences of Hepatitis B Serological Tests in Cirrhosis and Hepatocellular Carcinoma Patients - Yuyun Widaningsih; Mutmainnah Mutmainnah; Rika Adriati Datu Adam (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Cirrhosis and hepatocellular carcinoma (HCC) are the most common complications of chronic hepatitis B. Hepatitis B Virus (HBV) reactivation occurs in the inactive phase, characterized by reappearance of HBsAg or negative HBsAg. The prevalence of occult hepatitis B infection in cirrhosis and HCC ranges from 20% to 60%. This study aimed to analyze the differences in hepatitis B serological tests in patients with cirrhosis and HCC for diagnosis of acute or chronic hepatitis B. The current research was analytical and descriptive with a cross-sectional study design. This study involved 177 patients, including 50 cirrhosis patients and 127 HCC patients. Hepatitis B serological tests (HBsAg, HBeAg, anti-HBe, total anti-HBc) were analyzed using VIDAS instruments by the Enzyme-Linked Fluorescent Immunoassay (ELFA) method. Hepatitis B serological test results were grouped based on the interpretation of serological test results. The data were processed with the statistical test Kolmogorov-Smirnov test, independent T-test, and Chi-Square, and results with p<0.05 were reported as significant. This study found that most males suffer from cirrhosis and HCC due to chronic HBV infection, with a mean age of 57. Chronic hepatitis was most common in patients with cirrhosis and HCC  (71.2%). There was no significant difference in the interpretation of the hepatitis B serological test between patients with cirrhosis and HCC, with a p-value of 0.230 (p > 0.05). There was no significant difference in interpreting the hepatitis B serological test between cirrhosis and HCC. Both reactive HBsAg and non-reactive HBsAg can be obtained in cirrhosis and HCC.